(untitled) (Theatrum historiae, 2010)
On around June 20th 1542, near Chlumec nad Cidlinou (at that time the estate of Jan of Pernštejn) two suspects were arrested: Jan Krška and the tavern-keeper Pavel of Nový Hrádek (district of Náchod). When interrogated on the rack, both confessed to having been involved in an attack on a convoy of Jews who, at the order of the Bohemian Landtag and King Ferdinand I, were being forced to leave the country. Jan Krška confessed to other crimes, including involvement in the counterfeiting of money at Žampach Castle (district of Ústí nad Orlicí). Owing to the severity of this crime the case was passed on to Jan of Pern- štejn’s estate officials in Pardubice. There, when questioned on the rack, a statement was wrung out of a tavern-keeper from Starý Ples (district of Hradec Králové), Jiří Vodička, who had been arrested as an accomplice on the basis of the confessions made by the aforementioned criminals. On July 10th 1542 Jan Krška and Jiří Vodička, convicted of counterfeiting money, were burnt at the stake in Pardubice; Pavel of Nový Hrádek was hung for his offences. The main person behind the counterfeiting workshop, the smith Jan of Žampach, was then arrested. On July 20th he was interrogated on the rack in the royal town of Vysoké Mýto (district of Ústí nad Orlicí) and was also burnt there on the same day. The statements of all four criminals were transcribed in the Achtbuch kept in Pardubice. The study analyses the statement records and attempts to reconstruct the work of the counterfeiting workshop at Žampach Castle as well as the circumstances surrounding the raid on the Jews. The counterfeiting workshop operated from 1537 to 1538, possibly between 1536 and 1539, in the cellars of the then unoccupied Žampach Castle. The smith Jan was assisted by the journeyman Jan Smolík and the aforementioned Jan Krška, who also distributed the counterfeit money further afield. Other partners in crime (the tavern-keeper Vodička and others) supplied the counterfeiters with sheet copper and copper pots, which were generally stolen. In the workshop they minted Görlitz black money, Viennese money (1⁄2 kreutzer) and the Austrian groschen (3 kreutzers). These forgeries were exchanged for real money at the ratio of 2 : 1. When questioned, they gave the names of 24 people to whom they had passed on counterfeit money, in some cases on several occasions. We can only make a hy- pothetical estimate of how much money was counterfeited at the workshop at Žampach, but we assume they minted roughly 10-20 thousand coins. The testimony of Jiří Vodička also implies that there was a workshop counterfeiting small coins in the village of Úhlejov (district of Jičín), which can be dated approximately to 1510-1530; the tavern-keeper Vo- dička also met distributors of small counterfeit Polish coins. From the statements of Jan Krška, Jiří Vodička and Pavel of Nový Hrádek we can reconstruct two attacks on convoys of Jews who, in June 1542, after being expelled from Bohemia, were travelling to Silesia and on to Poland. Both attacks were made by a group of 50-60 bandits (the statements list the names of almost 35 people from 15 localities). The core of the group consisted of the inhabitants of villages and towns on the road leading from Dobruška to Nový Hrádek below Frymburk and then on to Olešnice in the Orlické Mountains (Adlergebirge) and from there to Homol in Kłodzko (Poland). The bandits first attacked below Homol, where the Polskie Wrota pass begins on its route inland towards Kłodzko. The core of the same group, probably emboldened by the success of the assault at Homol, held up another convoy of Jews on their way to a more remote destination deep within Eastern Bohemia. The meeting point was at Jiří Vodička’s tavern in Starý Ples. The attack took place on or just before June 20th 1542 on Chloumek Hill in the cadastre of Habřina (district of Hradec Králové). This assault was evidently not as successful, as it was at least partially dispersed by the armed escort of the Jewish convey, as can be seen from the fate of Jan Krška and Pavel of Nový Hrádek, who were captured while on the run somewhere near Chlumec nad Cidlinou. This reconstruction greatly enhances our know- ledge of the unsettled events surrounding the exodus of the Jews from Bohemia in 1542.